2022
DOI: 10.3390/iot3010012
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Detection and Resolution in IoT Systems: A Survey

Abstract: Internet of Things (IoT) systems are becoming ubiquitous in various cyber–physical infrastructures, including buildings, vehicular traffic, goods transport and delivery, manufacturing, health care, urban farming, etc. Often multiple such IoT subsystems are deployed in the same physical area and designed, deployed, maintained, and perhaps even operated by different vendors or organizations (or “parties”). The collective operational behavior of multiple IoT subsystems can be characterized via (1) a set of operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The works [6,[8][9][10], and [11] indicated that the present SASs are capable of detecting and resolving conflicts between adaptation rules at runtime. However, further enhancing SAS's adaptive capacity requires a significant increase in the number of adaptive rules, resulting in determining solutions for the conflicts becoming more complex and consuming time.…”
mentioning
confidence: 90%
“…The works [6,[8][9][10], and [11] indicated that the present SASs are capable of detecting and resolving conflicts between adaptation rules at runtime. However, further enhancing SAS's adaptive capacity requires a significant increase in the number of adaptive rules, resulting in determining solutions for the conflicts becoming more complex and consuming time.…”
mentioning
confidence: 90%
“…A communication infrastructure and computing units are required to implement the Internet of Things concept [2]. IoT storage, connectivity, and computing provisioning are all made possible by cloud computing [3,4].…”
Section: Introductionmentioning
confidence: 99%